1963
DOI: 10.1172/jci104708
|View full text |Cite
|
Sign up to set email alerts
|

The Experimental Induction in Man of Sensitivity to Leucine Hypoglycemia*

Abstract: In 1956, Cochrane, Payne, Simpkiss, and Woolf (1) reported that oral administration of L-leucine induces a sharp fall in blood glucose levels in some children with idiopathic familial hypoglycemia, but that it has no effect in normal subjects. Flanagan, Schwartz, and Ryan (2) were the first to report that oral administration of L-leucine to patients with functioning islet-cell tumors also produces a hypoglycemic effect. By the immunoassay of Yalow and Berson for measurement of plasma insulin, an increase has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
38
1
1

Year Published

1963
1963
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 19 publications
6
38
1
1
Order By: Relevance
“…Administration of leucine to chlorpropamidepretreated subjects is a strong stimulus for insulin release and consequent hypoglycemia, as has been reported previously from this laboratory (14)(15)(16). This is demonstrated again by the data derived from the seven infusions of leucine before administration of benzothiadiazines (Table II, Figure 1).…”
Section: Healthy Subjectssupporting
confidence: 73%
See 1 more Smart Citation
“…Administration of leucine to chlorpropamidepretreated subjects is a strong stimulus for insulin release and consequent hypoglycemia, as has been reported previously from this laboratory (14)(15)(16). This is demonstrated again by the data derived from the seven infusions of leucine before administration of benzothiadiazines (Table II, Figure 1).…”
Section: Healthy Subjectssupporting
confidence: 73%
“…We (14,15) have shown that when leucine is given to chlorpropamide 3-pretreated healthy subjects hypoglycemia together with a sharp increase in plasma insulin occurs. We have also shown that increased release of insulin from the pancreatic beta cells is the mechanism by which leucine increases peripheral levels of insulin (16).…”
mentioning
confidence: 97%
“…We conclude that 1) ingestion of protein meals results in significant increases in plasma insulin, 2) these increases in plasma insulin cannot be accounted for solely or even largely by the effect of l-leucine contained in the meals, and 3) ingestion of protein and rising plasma levels of certain amino acids appear to be associated with a physiologic stimulus for insulin release.…”
Section: Discussionmentioning
confidence: 85%
“…On the other hand, after pretreatment with Novo Ultralente insulin, administration of leucine produced decreases in blood glucose levels that, although significant, were small and inconsistent. A modest but significant hypoglycemic effect was also produced in some healthy subjects by administering leucine without prior administration of hypoglycemic agents ( 1,2). The magnitude of these decreases in blood glucose levels was similar to that observed after administration of leucine to subjects pretreated with Ultralente insulin.…”
mentioning
confidence: 99%